The German Shakespeare (American International Journal of Humanities, Arts and Social Sciences, 2020)
Over The past four hundred years, Shakespeare has played a significant role within a European framework, particularly, where a series of political events and ideologies were being shaped. The birth of the nation during the late 18th and 19th centuries, the first and second world wars, the process of European unification during the 1990s, are a case in point. This part challenges the idea of an all-encompassing universal Shakespeare by demonstrating that Shakespeare and his plays transmitted across different histories, languages, and traditions meant something significantly different in these geographical contexts. Rejecting the existence of a universally absolute and singular Shakespearean meaning, I attempt to demonstrate that Shakespeare is always what he is imagined to be in a cultural and historical context. The various local and national appropriations and the universality of the cultural icon, “Shakespeare”, clash in the daily practice of interpreting, performing, and teaching his plays. This paper discusses Shakespeare’s appropriation and performance in East Germany. It focuses on the theatrical production and its cultural context in this country.